Compensation for damage caused by the commission of offenses against the environment - Ćorović, Emir; Mrvić, Milena (Glasnik Advokatske komore Vojvodine, 2025)
In the legal system of the Republic of Serbia, the environment is also protected through criminal law, more precisely by the norms of criminal and misdemeanor law, as well as law governing economic offenses. Committing an environmental offense may also result in corresponding damage. This concerns the civil law consequences arising from the commission of the offenses in question. Compensation for damage caused by environmental offenses can be achieved out of court and through court. It can also be done before the court in two ways: 1) in the criminal proceedings itself, based on the submitted property claim (so-called adhesion proceedings) and 2) in civil proceedings after the criminal proceedings have ended. Therefore, the paper discusses certain issues related to the characteristics of this damage, and the corresponding issues related to the procedure for realizing its compensation. In order to adequately consider this matter, it was necessary to briefly point out the features of the protection of the environment through penal law.